CXCL4-induced plaque macrophages can be specifically identified by co-expression of MMP7+S100A8+ in vitro and in vivo: $hChristian Erbel, Mirjam Tyka, Christian M. Helmes, Mohmmadreza Akhavanpoor, Gregor Rupp, Gabriele Domschke, Fabian Linden, Antonia Wolf, Andreas Doesch, Felix Lasitschka, Hugo A. Katus and Christian A. Gleissner - Erbel, Christian; Tyka, Mirjam Evelin; Helmes, Christian Michael; Akhavanpoor, Mohammadreza; Rupp, Gregor Fabian; Domschke, Gabriele; Linden, Fabian; Wolf, Antonia; Dösch, Andreas; Lasitschka, Felix; Katus, Hugo; Gleißner, Christian A. (Innate immunity, 2015)
Macrophage heterogeneity in human atherosclerotic plaques has been recognized; however, markers for unequivocal identification of some subtypes are lacking. We found that the platelet chemokine CXCL4 induces a unique macrophage phenotype, which we proposed to call ‘M4’. Here, we sought to identify suitable markers that identify M4 macrophages in vitro and in vivo. Using a stringent algorithm, we identified a set of potential markers from transcriptomic data derived from polarized macrophages. We specifically focused on matrix metalloproteinase (MMP)7 and S100A8, the co-expression of which has not been described in any macrophage type thus far. We found dose- and time-dependent MMP7 and S100A8 expression in M4 macrophages at the gene and protein levels. CXCL4-induced up-regulation of both MMP7 and S100A8 was curbed in the presence of heparin, which binds to CXCL4 and glycosaminoglycans, most likely representing the macrophage receptor for CXCL4. Immunofluorescence of post-mortem atherosclerotic coronary arteries identified CD68+MMP7+, CD68+MMP7−, CD68+S100A8+ and CD68+S100A8− macrophages. A small proportion of MMP7+S100A8+ macrophages most likely represent M4 macrophages. In summary, we have identified co-expression of MMP7 and S100A8 to be a marker combination exclusively found in M4 macrophages. This finding may allow further dissection of the role of M4 macrophages in atherosclerosis and other pathologic conditions.